Manejo de la regeneración natural de la especie Himenaea oblongifolia Huber “azúcar huayo” con biofertilizantes en vivero de Puerto Almendra, Loreto, Perú, 2024 - Pacaya Mananita, Katherin Carolina (2025)
The study was conducted at Puerto Almendra Forestry Research and Training Center (CIEFOR) nursery, part of the National University of the Peruvian Amazon (UNAP), to evaluate the management of natural regeneration of the Himenaea oblongifolia Huber “Azucar huayo” species through the use of biofertilizers in the Puerto Almendra nursery for the production of Azucar huayo seedlings. According to the obtained results: Constant linear growth was not observed in the control. Growth between 15 and 30 days was lower that at the other intervals, with the most notable beinng between 75 and 90 days. Treatment T1 showed the best results, with a consistently higher increase than the other treatments. T2 maintained moderate growth, while the control had the lowest performance. Height growth with biofertilizer was 15.42% compared to the control, while T2, a 40:40:20 substrate alone, increased height growth by 5.12% compared to the control. The null hypothesis is not rejected since there is no statistically significant evidence to support the existence of differences between the beds (T1-bed1,T1-bed2, and T1-bed3) in terms of growth.